Orthogonal wear experiment of 13Cr-L80 tubing string in high-yield gas wells and analysis of its influencing factors. (July 2021) - Guo, Xiaoqiang; Liu, Jun; Dai, Liming; Huang, Liang; Wei, Anchao; He, Yufa; Fang, Dake
Highlights: An orthogonal wear experiment was performed on the 13Cr-L80 tubing string. The wear patterns of the tubing-casing were primarily abrasive and adhesive wears. The wear life can be augmented by reducing contact load and vibration displacement. The vibration frequency of tubing string should be maintained below 1.5 Hz. The completion fluid should be set as approximately 1.2 g/cm 3 on-site. Abstract: Due to wear failures caused by tubing string vibrations in high-yield gas wells, an orthogonal wear experiment was performed on the 13Cr-L80 tubing string. The influence of contact load, friction frequency, wear time, completion fluid density, and reciprocating stroke length on the wear characteristics of the tubing string were effectively analyzed using range analysis, variance analysis and the control variable methods. The results demonstrate that, the wear patterns of the tubing-casing were primarily abrasive and adhesive wears, with minimal corrosion wear. In-field operations, the service life of the tubing string in high-yield gas wells can be effectively augmented by reducing the contact load and longitudinal vibration displacement of the tubing-casing, maintaining the vibration frequency of the tubing string below 1.5 Hz, and utilizing a completion fluid with a higher density (approximately 1.2 g/cm 3 ). The wear amount and friction coefficient of the tubing string are primarily influenced by the contact load and reciprocating stroke length, respectively. Moreover, the effect significances of the contact load and reciprocating stroke length were particularly significant and significant, respectively. These results provide useful guidance for designing and implementing approaches to improve the service life of tubing strings in high-yield gas wells.